THE POWER OF TAX INCENTIVES ON MOTORIZED VEHICLE TAX COMPLIANCE MODERATED BY TAX SOCIALIZATION IN EAST JAVA - Limantoro, Amedea Cristabel; Iswati, Sri; Rahmiati, Alfa (Jurnal Akuntansi dan Keuangan Indonesia, 2022)
During the Covid-19 pandemic, the Indonesian government issued tax incentive policies to ease the burden on the community while increasing revenue at the central and local tax levels. Due to the policy regarding the PKB (Pajak Kendaraan Bermotor or Motorized Vehicle Tax) tax incentive that was applied during the Covid-19 pandemic, the researchers aimed to examine the relationship of the PKB tax incentive on tax compliance of motorized vehicle users in East Java during the pandemic period from 2020 to 2021 moderated by tax socialization. This study used samples of taxpayers who own motorized vehicles, both two-wheeled or four-wheeled, whose domiciled in East Java. The samples were taken by using the purposive sampling technique. The data source was taken from primary data obtained from the questionnaires and was analyzed using simple linear regression and moderated regression analysis. The result of this study showed that the PKB tax incentive has relationship on motorized vehicle users’ tax compliance; meanwhile tax incentive which moderated by tax socialization weakening the relationship of the PKB tax incentive on motorized vehicle users’ tax compliance during the Covid-19 pandemic in East Java.